PROGRAM TRAINING & DEVELOPMENT BERBASIS SPIRITUALITAS - Siswanto, Siswanto (Fakultas Ekonomi, UIN Maliki Malang, 2008)
This paper attempts to explain the role of spirituality in workplace to reach highly organization performance. The currently challenge both profit and non-profit organization is how to develop human resource. That’s so urgent because it’s a valuable asset. Three ways to develop human resource consists of training and development, organization development, and career development. The intent of this paper is to integrate spirituality in training development program. Spirituality in workplace has relationship with attitude and organization behavior dimension (Milliman et.al. 2003). Dimension of organization behavior encompass organization commitment, intention to quit, intrinsic work satisfaction, job involvement, and organization-based self-esteem. The paper concludes that training development based-spirituality will contribute to long term behavior/attitude change.